Dynamics of Potassium Release and Adsorption on Rice Straw Residue - Li, Jifu; Lu, Jianwei; Li, Xiaokun; Ren, Tao; Cong, Rihuan; Zhou, Li (PloS one, 2014)
Straw application can not only increase crop yields, improve soil structure and enrich soil fertility, but can also enhance water and nutrient retention. The aim of this study was to ascertain the relationships between straw decomposition and the release-adsorption processes of K(+). This study increases the understanding of the roles played by agricultural crop residues in the soil environment, informs more effective straw recycling and provides a method for reducing potassium loss. The influence of straw decomposition on the K(+) release rate in paddy soil under flooded condition was studied using incubation experiments, which indicated the decomposition process of rice straw could be divided into two main stages: (a) a rapid decomposition stage from 0 to 60 d and (b) a slow decomposition stage from 60 to 110 d. However, the characteristics of the straw potassium release were different from those of the overall straw decomposition, as 90% of total K was released by the third day of the study. The batches of the K sorption experiments showed that crop residues could adsorb K(+) from the ambient environment, which was subject to decomposition periods and extra K(+) concentration. In addition, a number of materials or binding sites were observed on straw residues using IR analysis, indicating possible coupling sites for K(+) ions. The aqueous solution experiments indicated that raw straw could absorb water at 3.88 g g(-1), and this rate rose to its maximum 15 d after incubation. All of the experiments demonstrated that crop residues could absorb large amount of aqueous solution to preserve K(+) indirectly during the initial decomposition period. These crop residues could also directly adsorb K(+) via physical and chemical adsorption in the later period, allowing part of this K(+) to be absorbed by plants for the next growing season.